Patriotism in Samples of Poetry Published in Israel in the 1970s - Guledan, Lali ("Intercultural Dialogues" Transactions, 2023)
In the 70s of the last century, the first wave of Georgian Jews left Georgia for their historical homeland - Israel. It is known that Georgian Jews have been speaking the Georgian language for many centuries. However, their Georgian is linguistically distinct from standard Georgian but these distinctive linguistic features are gradually disappearing due to the migration of Jews to their historical homeland. The Georgian language literature created in Israel is directly related to the language of Georgian Jews, and can also be lost together with it, therefore it has crucial important to analyze the works of Georgian Jewish writers created in the written language, which is in danger of extinction, and in general, to research the printed products (writing, periodicals, etc.) that are created by Georgian Jews in Israel. In the 1970s the newspaper “Aliyah” was founded by the Georgian Jews in Israel. This newspaper is primarily concerned with the news related to the Jewish-Georgian community and their achievements, their cultural events, the world and Israeli news, useful guidelines and instructions for the new repatriates, etc. Over time the section of literature became richer and more versatile. Unlike all other periodicals printed in Israel, “Aliyah” covered a broad range of works by Jewish-Georgian authors. Many poets and writers first appeared on its pages and gradually became more and more famous and refined in their craftsmanship. Their work is a good source for literary studies. In the article, we discuss the works of Georgian Jewish poets of the 70s, mainly the samples of poetry published in “Aliyah”, since it was the only Georgian-language publishing body in Israel in the 70s. . The samples of the presented poetry are thematically diverse, but poems written on patriotic themes predominate, and this is natural. Jews from different countries of the world were united by the boundless love of their historical homeland. In the samples of poetry published by Georgian Jews in Israel, which are mainly written in the fluent Georgian language, the love of the motherland - patriotism is presented in diverse and versatile ways. Recalling the past of the Israelis, emphasizing the modern problems, the spirit of resistance to the enemies, the boundless respect of the heroes and the Israeli army, and the strong desire to establish peace, nostalgia for Georgia, raising the topic of two homelands and other nuances, accurately reflect the psychological state and creative skills of the Jews from Georgia, which makes it possible to assert that in the 70s, despite the fact that Jewish concepts and Hebrew vocabulary are abundantly intruded into their poetry, Georgian Jewish poets and writers still stand firmly on Georgian writing traditions.